EXPLORING PRE-SERVICE TEACHERS EXPERIENCES TOWARDS SYNCHRONOUS ONLINE LEARNING AMIDST THE COVID-19 PANDEMIC - Rahmawati, Fitria (English Review: Journal of English Education, 2022)
As a result of the COVID-19 pandemic, learning systems all around the world have shifted from traditional classrooms to online learning. Synchronous learning was developed to promote online learning interactions via audio, video, text chat, interactive whiteboards, and app-sharing audio, video, and text chat. This study focused on how the English Language Education Department (ELED) pre-service teachers experience participating in synchronous online learning during the covid-19 pandemic. The participants involved in this research were six ELED pre-service teachers. This research was conducted at English Language Education Department at one Islamic Private University in Yogyakarta. As a research design, the researcher used descriptive qualitative. The information was obtained through an interview. The result showed that pre-service teachers participated in synchronous online learning activities such as listening to lectures, doing a group discussion, doing a presentation, and completing evaluations. There were also various tools that made learning easier for pre-service teachers, such as sharing screen, recording, camera, and microphone. Regarding the perceptions of the ELED pre-service teachers, this study revealed some positive impacts and negative impacts of synchronous learning as perceived by the pre-service teachers. The positive impacts were flexibility in learning, a variety of ways of learning, live interaction, and more autonomous learning. Otherwise, the negative impact of synchronous learning was missed learning activity, lack of interaction, undelivered messages, and feeling isolated.